Management of streaming multimedia content using mobile agent technology on pure P2P-based distributed e-learning system. (1st January 2014) - Higashino, Masayuki; Hayakawa, Tadafumi; Takahashi, Kenichi; Kawamura, Takao; Sugahara, Kazunori
Nowadays, many e-learning systems are widely deployed in educational schools. Typical e-learning systems are implemented as the client-server model, but it requires an expensive central server for scalability. Thus, in order to reduce the load on the central server, we have been developing a pure P2P-based distributed e-learning system. All learning contents are realised as mobile agents in this system, which works by interactions of mobile agents. However, it is not enough that data are simply distributed learning contents into nodes. Since the size of multimedia content is different, it makes imbalances of resource usage among nodes. Additionally, users cannot play smoothly multimedia contents. Therefore, we propose a method that divides a multimedia content into small fragments, keeps links of locations among these fragments and caches these fragments in nodes.